Assessment of the Effectiveness of Health Education and Screening Test in Reducing Multiple Myeloma in the Middle-Elderly Nigerians – The Rational for Proposed Study - Nwabuko, Ogbonna; John, Raphael Edoka (British Journal of Healthcare and Medical Research, 2022)
The developing countries including African union bear the highest global burden of cancer. Multiple myeloma which accounts for 1-2% of all cancers globally is grossly under-diagnosed in this part of the world. In Nigeria, it poses diagnostic dilemma to the target population and therapeutic challenge due to late presentation of the few newly diagnosed cases. This could be as a result of inability of the national cancer control framework to activate the priority areas of actions on its control. This study proposal highlights the rationale for conducting a public health education and screening test for multiple myeloma in Nigeria and the immediate and long-term benefits of this strategic leadership approach of reducing the burden of multiple myeloma in the country. Scholarly articles indexed in PubMed, MedLine, Google Scholar, African Journal Online (AJOL) databases were searched using ‘’multiple myeloma and rational for screening’’ as medical subject headings. This paper presented a synthesis of the reviewed articles and the expected outcomes of possible interventions on the burden of multiple myeloma disease in Nigeria. The study report was analysed and grouped according to the following categories: problem statement and rationale, strategic ways education and screening for myeloma can improve its survival outcome in Nigeria, study strengths and weaknesses, proposed study design (Descriptive cross-sectional study design), research methodology linked to the study designs and their pros and cons to research question. Conclusion: This study proposal will serve as a public health safety measure for reducing the burden of multiple myeloma in Nigeria. The hallmark of the study outcome may be useful in strengthening the health institutions in Nigeria to manage multiple myeloma effectively.